Linguaggio sensibile al genere in prospettiva lessicografica: osservazioni didattiche sulla “Leichte Sprache” e sul “Linguaggio facile italiano” - Valentina Crestani (MediAzioni)
The essay focuses on gender-sensitive language in German and Italian from a lexicographic perspective. Research questions are: 1. How can the results of lexicographic research be integrated into the didactics of translation (German as L2) in university lectures? 2. What tools can support mediating human nouns in German-Italian / Italian-German translation activities in simplification contexts? The analysis considers (a) monolingual and bilingual dictionaries, which are based on a binary concept of gender; (b) "gender dictionaries", which go beyond binarism, at least for specific terms; (c) bilingual "easy language" dictionaries that adopt different gender-sensitive language strategies. The analysis highlights differences in the treatment of a selection of human nouns in dictionaries (a), the different availability of lexicographical tools dedicated to gender-sensitive language (b) and translation issues (c). Language learning activities in translation are to be centred on the balance between the benefits of knowledge of gender-sensitive language strategies, described in manuals and websites dedicated to the topic, and the problems/risks in applying such strategies, especially in mediation contexts that pursue the primary objective of simplification.